Occurrence and Characterization of Escherichia coli Isolated from Diarrhoeic Piglets in Meghalaya - Shakuntala, I.; Sanjukta, R. K.; Das, S.; Puro, K.; Ghatak, S.; Rajkhowa, S.; Milton, A. A.P.; Sen, A. (Indian Journal of Hill Farming, 2018)
The present study was conducted to investigate the occurrence of Escherichia coli carrying virulence genes and antibiotic resistance associated with piglet diarrhea in Meghalaya. We analysed 294 faecal samples randomly collected from the piglets with history of diarrhoea for the isolation of E. coli followed by screening of virulence genes among the isolates by specific and multiplex PCR. Further E. coli isolates were subjected to Kirby–Bauer disc diffusion method to study phenotypic antibiotic resistance. The overall occurrence rate of E. coli was 51.7% (152/294). Among 152 isolates virulence factor genes detected were stx1 (0.6%), stx2 (7.2%), lt (1.97%), stx2e (3.9%), eae (15.1%), STaP (0%), K99 (0%), fliCH7 (0.6%) and hlyA (15.1%). Based on multiplex PCR, out of these 152 isolates ,18 (11.8 %), 2 (1.3%) and 23 (15.1%) isolates were recorded as Shiga-toxin-producing E. coli (STEC), atypical enteropathogenic E. coli (EPEC) and enterotoxigenic E. Coli (ETEC), respectively. Antibiotic resistance percentages for Metronidazole, Sulphafurazole, Tetracycline, Streptomycin, Trimethoprim, Neomycin, Ampicillin, Co-trimoxazole, Ceftazidime, Enrofloxacin, Chloramphenicol, Ceftriaxone, Ciprofloxacin and Gentamicin were found to be 100, 70, 68.2, 61.7, 44.8, 35.5, 34.6, 29, 25.2, 14, 10.3, 10.3, 6.5 and 3.7, respectively. In conclusion, this study showed the frequency of virulence genes, pathotype and antimicrobial resistance in E. coli strains isolated from diarrhoeic piglets in Meghalaya.